Autotrophic picoplankton in mesozooplankton guts: evidence of aggregate feeding in the mesopelagic zone and export of small phytoplankton - Wilson, S. E.; Steinberg, D. K. (Marine Ecology Progress Series, 2010)
Zooplankton play a key role in affecting the efficiency by which organic matter is exported to depth. Mesozooplankton consumption of detrital aggregates has been hypothesized as a mechanism for enhancing the export of picoplankton from surface layers. We analyzed the gut contents of mesopelagic copepods and ostracods using light and epifluorescence microscopy to determine if cyanobacteria and eukaryotic phytoplankton too small to be ingested individually were present. Hind-guts were dissected from multiple species collected in discrete depth intervals between 0 and 1000 m during the day and night, at contrasting sites in the subtropical (Hawaii Ocean Time-series site ALOHA) and subarctic (Japanese time-series site K2) Pacific Ocean. Autofluorescing cyanobacteria and small eukaryotic phytoplankton were found in the guts of nearly all species sampled from all depths, indicating consumption of aggregates. Some of the cyanobacteria and other small cells ingested may have originated from inside the guts, or as symbionts, of microzooplankton, which were also common in the guts of many of these species. At both sites, most species' guts contained higher concentrations of cyanobacteria and small phytoplankton at night than during the day. Ostracod guts at ALOHA contained higher densities of picoplankton than those at K2, reflecting the predominance of smaller cells at ALOHA. Guts of diel vertical migrators still contained picoplankton at their deep, daytime residence depths, indicating active export of these cells. Our results indicate mesozooplankton grazing on aggregates is a pathway by which flux of picoplankton can be enhanced.